The Use of Banyumas Centrosema pubescens Compost and Ajibarang’s Phosphate Rock to Kandiudults for Soybeans Amelioration - Widyasunu Purwandaru; Maryanto Joko; Widarawati Rosi (BIO Web of Conferences)
Kandiudults is intensively weathered soil with low in pH and clay activity, though is high of H+ and Al3+ activities. Hydrolysis of Al3+ affects soil acidity and H+ both are increasingly. Change to better chemical properties is key to increase the productivity by decreasing it’s positively charge by adding negative functional of “like-humus” organic fertilizer as a one key way technology to adapt climate change. The research was aimed to know effect local Centrosema pubescens (Cp) compost and Phosphate Rock Banyumas for Kandiudults improvement by increasing it’s: (i) chemical properties, (ii) P soils availability and P absorption by soybean though to its quality, and (iii) to find best dose of compost and Phosphate Rock. Research was done under plastic house Fac. of Agriculture – UNSOED, Purwokerto. Materials used: (i) low activity of Krumput Banyumas Kandiuldults, (ii) the Cp compost from Krumput, Banyumas, and (iii) Slamet soybean variety. Randomized complete block design was employed with factorial combination by 3x3 with three replicates though it had 27 polybag units. Research result: (i) Cp compost effect on soil pH, CEC, and exchangeable-Al, P-uptake by plant and grain soybean protein-N; (ii) Phosphate Rock effect on soil pH, exchangeable-Al, and CEC, it affect P-uptake by plant, grain soybean protein-N, crop dry weight, and grain dry weight. These results were induced that: “like-humus” of Cp producing compost was able to manage the negative charge of Krumput’s Kandiudults though it meant increasing of its positively charge.